COVID-19 in congenital heart disease patients: what did we learn?! - Rana Zareef; Rana Zareef; Elio Salameh; Rawan Hammoud; Theresia Tannouri; Theresia Tannouri; Theresia Tannouri; Fadi Bitar; Fadi Bitar; Fadi Bitar; Mariam Arabi; Mariam Arabi; et al. (Frontiers in Cardiovascular Medicine, 2023)
AimCOVID-19 pandemic has spread widely at unpreceded pace. Cardiovascular comorbidities are significantly correlated with severe and critical illness. Nevertheless, studies examining the impact of congenital heart disease on COVID-19 severity are scarce and restricted to hospitalized patients. This study aims to explore the course of COVID-19 illness, severity and complications in patients with concomitant congenital heart disease.MethodologyThis study is a cross sectional survey that includes patients with congenital heart disease who are registered at the Children Heart Center at the American University of Beirut Medical Center. The survey was conducted in the pediatric cardiology outpatient clinics or remotely via phone calls.ResultsA total of 238 patients participated in the study, of which 47.9% had suspected or confirmed diagnosis of SARS-CoV-2 infection. The majority of patients had mild illness. The symptoms ranged between rhinorrhea (15.6%), cough (15.6%), low-grade fever (11.2%), anosmia (2.7%), ageusia (2.5%), headache (9.8%), high-grade fever (8.5%), gastrointestinal symptoms (7.6%), lethargy (6.3%), muscle aches (5.6%), difficulty breathing (5.4%), joint pain (4.7%), and chills (4.7%). 20% of the surveyed patients required treatment at home. Hospitalization and oxygen therapy was required in 3.5% of cases, while only 1.5% demanded intensive care admission. Only one fatality was encountered.ConclusionCOVID-19 infection in pateints with congenital heart disease exhibits a mild to moderate course, and doesn't necessarily increase risk of complicated disease. No correlation could be found between specific congenital heart lesion and disease severity.